Дослідження пам’яток культури лінійно-стрічкової кераміки на Волині - Пясецький, В.К.; Охріменко, Г.В. (Археологія, 1990)
Публікацію присвячено охоронним дослідженням вперше відкритого на території нашої країни поселення: старшої лінійно-стрічкової кераміки в м. Рівне та двом поселенням на Волині, що відносяться до нотного етапу розвитку КЛСК. 1983 г. авторами статьи начаты раскопки трех поселений культуры линейно-ленточной керамики: Ровно на р. Устя, Клевань на р. Стубла (оба в бассейне р. Горынь) и Гирка Полонка на р. Черногузка (бассейн р. Стырь). Поселения находятся в пределах Волынской лесовой возвышенности. В Ровно установлено два этапа существования поселения: более ранний и очень короткий с ямами-полуземлянками и следующий за ним продолжительный с наземными жилищами имеющими в плане размеры около 10,0X3,0 м. Остатки небольшого наземного строения обнаружены на поселении Клевань. На поселении Гирка Полонка жилище представляло собой двухкамерную полуземлянку общей длиной 7,8 м и шириной около 3,7 м.
Особенности керамики ровенского поселения позволяют отнести его к ранней (старшей) ступени развития культуры линейно-ленточной керамики и датировать по некалиброванной шкале радиоуглеродных дат первой половиной (но ближе к середине) — серединой V тыс. до н. э. Это первое столь раннее поселение на территории нашей страны. Поселения Гирка Полонка и Клевань относятся к младшей фазе развития этой культуры. Наличие во многих случаях в керамике из Гирка Полонки примеси половы может указывать, что это поселение древнее, чем Клевань. The authors of the paper began in 1983 excavations of three settlements associated with linear-band ceramic culture: Rovnoye on the Ustya river, Kievan on the Stubla river (both in the Goryn river basin) and Girka Polonka on the Chernoguzka river (the Styr river basin). The settlements are located within the Volyn loessian hills. Two stages of existence are established in the Rovnoye settlement: an earlier, very short, period with pits-half- mud-huts and a later, long-term, period with overground dwellings 10.0X3.0 m in the plan. The remains of a little overground bulding were found in the settlement of Kievan. In the settlement of Girka Polonka the dwelling looked like a two-chamber half-mud-hut 7.8 m long and 3.7 m wide.
Peculiarities of the Rovnoye ceramics permit referring it to the early (older) stage in the development of linear-band ceramic and dating it back to the first half (closer to the middle)—the middle of the 5th Millenium В. C. (according to the noncalibrated scale of radiocarbon dates). This is the first early settlement in the territory of our country. The settlements of Girka Polonka and Kievan are related to the younger phase in the development of this culture. The availability of straw additions in the ceramics from Girka Polonka can indicate thas this settlement is more ancient that the Kievan one.